2001
DOI: 10.1002/ijc.1636
|View full text |Cite
|
Sign up to set email alerts
|

High expression levels of collagenase‐1 and stromelysin‐1 correlate with shorter disease‐free survival in human metastatic melanoma

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes capable of degrading extracellular matrix. Their role has been emphasized in tumor invasion, metastasis and tumor-induced angiogenesis. We studied the expression of collagenase-1 (MMP-1), stromelysin-1 (MMP-3) and collagenase-3 (MMP-13) in 70 melanoma metastases obtained from 56 patients treated with combined chemoimmunotherapy. The patients were divided into 2 groups using a cut-off point of 0% for MMP-1 expression and 20% for MMP-3 expression. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 55 publications
3
86
2
2
Order By: Relevance
“…In our previous studies, we have found that it was expressed tumor cells in human melanoma metastases (17,18). In the present study, we detected MMP-13 in the serum of patients with metastatic melanoma but also in the serum of healthy controls.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our previous studies, we have found that it was expressed tumor cells in human melanoma metastases (17,18). In the present study, we detected MMP-13 in the serum of patients with metastatic melanoma but also in the serum of healthy controls.…”
Section: Discussionsupporting
confidence: 66%
“…The expression of MMP-1 and MMP-13 (9), and the expression of gelatinases, in particular (10 -16), has been associated with melanoma progression. In our previous study, we found that high expression levels of MMP-1 and MMP-3 in melanoma metastases correlated with shorter disease-free survival (17). We also observed that a high expression of MMP-1 was associated with favorable treatment response (18).…”
mentioning
confidence: 70%
“…9 We have also found that high expression levels of MMP-1 or MMP-3 are associated with shorter disease-free survival in the same disease. 90 On the other hand, Arenas-Huertero et al 91 have found that low activity of MMP-2 or MMP-9 are associated with better response to neoadjuvant chemotherapy in SCC of oral cavity.…”
Section: Mmps As Prognostic Survival Markers In Cancermentioning
confidence: 98%
“…Abnormally elevated levels of MMP-1 or of both MMP-1 and MMP-13 have been associated with different types of cancers and with inflammatory diseases (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%